Penentuan kondisi optimal operasi deodorisasi bertahap untuk memaksimalkan retensi karoten dalam produksi minyak sawit merah (RPO) - Jefri Pandu Hidayat; Siti Munfarida; Rizka Lestari; Asful Hariyadi; Adrian Prananda Putra; Andini Angelina Putri; Ahmad Maulidi (AGROINTEK, 2026)
Red palm oil (RPO) is an intermediate superfood derived from palm oil, with the potential to reduce stunting and supply sustainable phytonutrients aligned with SDGs 4 in Ibu Kota Nusantara (IKN), East Kalimantan. RPO contains significantly higher carotene levels than commercial oils which is produced through physical modification processes to remove phospholipids and palm distinctive smell by beta-ionone. This study focuses on optimizing the deodorization process that removing impurity and volatile compounds. The optimization used Response Surface Methodology (RSM) with Central Composite Design (CCD) across 13 experimental runs, varying two key parameter temperature (118–133°C) and heating time (238–253 minutes). The novelty of deodorization process using multi-flash autovaporization by lower temperature for better preserve carotene. The effects on carotene content, free fatty acids (FFA), and density were analyzed using Design Expert 13 software. The optimal condition was found at 120°C for 240 minutes, resulting in 280 ppm carotene, 1.11% FFA, and a density of 0.948 g/cm³. The carotene kinetic model has been foundwhere X is temperature and Y is time. Statistical and graphical analysis confirmed that the final product met Indonesian standards SNI 3741:2013 and 9098:2022, which require FFA below 5% and carotene above 30 ppm.